Correlates of HPV Vaccination Intentions Among Adults Ages 27–45 Years Old in the U.S. - Thompson, Erika L.; Garg, Ashvita; Galvin, Annalynn M.; Moore, Jonathan D.; Kasting, Monica L.; Wheldon, Christopher W. (Journal of Community Health, 2021)
HPV vaccine is recommended for 27–45 year olds in the U.S. based on a shared clinical decision. This study examined knowledge, attitudes, and beliefs of adults 27–45 years old and the association with the likelihood of asking a healthcare provider about the HPV vaccine and the likelihood of getting the HPV vaccine. We conducted a cross-sectional survey of U.S. adults aged 27–45 years between April–May 2020 (n = 691). Primary outcomes were likelihood of asking their provider about the HPV vaccine and likelihood of getting the HPV vaccine. Demographic variables, knowledge, attitudes, and beliefs were covariates. Adjusted models were estimated for each outcome variable with a Poisson distribution and log function. More than half (55.7%) were likely to ask their provider about the HPV vaccine, but less than half (42.9%) were likely to get the HPV vaccine. Likelihood of asking their provider about the HPV vaccine was significantly associated with perceived likelihood of benefitting from the vaccine (aOR = 2.45; 95%CI = 1.69–3.57). Likelihood of receiving the vaccine was associated with attitudes (aOR = 1.04; 95%CI = 1.01–1.07), perceived effectiveness against HPV infection (aOR = 4.03; 95%CI = 1.20–13.53), and perceived likelihood of benefitting from the vaccine (aOR = 4.31; 95%CI = 2.64–7.03). Our findings suggest increasing positive attitudes, perceived effectiveness against infection, and perceived likelihood of benefitting from the vaccination are important factors to address when facilitating a shared clinical decision for HPV vaccination. Understanding factors associated with likelihood of discussing and receiving the HPV vaccine among people aged 27–45 years is important to successfully implement the guidelines for shared clinical decision-making.